INFERENCES ABOUT MANTLE MAGMA SOURCES FROM INCOMPATIBLE ELEMENT CONCENTRATION RATIOS IN OCEANIC BASALTS - Sims K.W.W.; DePaolo D.J. (My University, 1997)
It has been proposed that trace-element concentration ratios of basalts can be used like isotopic ratios to map the trace-element characteristics of mantle magma sources. We evaluate the assumptions and requirements of this approach and show that the magma source trace-element values inferred from data on basalts are dependent on the petrogenetic model assumed for the basalt. An approach to the analysis of incompatible element concentration ratio data is illustrated that uses the basalt data to obtain internally consistent fractionation models that take into account partial melting effects. The approach is applied to data on Ce/Pb and Nb/U in ocean island basalts (OIBs). Analysis of the basalt data in the literature provides evidence of substantial Ce/Pb fractionation during petrogenesis and a lesser amount of Nb/U fractionation. The estimated source compositions for OIBs in general are found to be consistent with their formation by admixture of (recycled) continental crustal material to the mantle, contrary to conclusions drawn previously from a less detailed analysis of the same data. We find that there are also correlations between trace-element composition and isotopic ratios that are consistent with continental crustal admixing. Other models for the magma source evolution may also be consistent with the data, but proper analysis requires specification of the petrogenetic parameters and consideration of the trace-element properties of the magma sources rather than the lavas. Large uncertainties in petrogenetic models translate to large uncertainties in source composition and weak constraints on the origins of the magma sources. Our analysis leads to estimates of the bulk partition coefficient for Pb (DPb); during mantle partial melting of spinel lherzolite source (DCe = 0.015), we calculate aDPb value of 0.035 +/- 0.009 (1σ) and a value of 0.028 +/- 0.009 (1σ) for partial melting of a garnet lherzolite source (DCe = 0.009). These values indicate that Pb is more compatible during mid-ocean ridge basalt (MORB) and OIB petrogenesis than previously thought from experimental studies of silicate crystal/melt distribution coefficients, suggesting possibly, that sulfide, present as either a residual mantle phase or as a shallow fractionating phase, strongly influences the partitioning of Pb.